FIAC 2000 : 200 expositions personnelles. - Chirac, Jacques; Forni, Raymond; Jaeger, Véronique; Lambert, Yvon; Tasca, Catherine (Paris : OIP (Organisation Idées Promotion), 2000)
Aguayo, Fermin ; Aillaud, Gilles ; Alberola, Jean-Michel ; Arden, Roy ; Arocha, Carla ; Arroyo, Eduardo ; Atlan, Jean-Michel ; Balzac, Alain ; Barbier, Gilles ; Barclay, Per ; Baselitz, Georg ; Beard, Peter ; Bedia, José ; Bejarano, Agustin ; Belin, Valérie ; Belle, Charles ; Ben ; Bernier, Pascal ; Bianchi, Domenico ; Bianco-Valente ; Blaufuks, Daniel ; Bloch, Pierrette ; Blume, Anna & Bernhard Johannes ; Bordarier, Stephane ; Botero, Fernando ; Braeckman, Dirk ; Brauner, Victor ; Brus, Günter ; Buraglio, Pierre ; Buren, Daniel ; Burri, Alberto ; Calle, Sophie ; Calvo, Carmen ; Cecchini, Loris ; Chadwick, Helen ; Chamberlain, John ; Charles, Hervé ; Chen Zhen ; Cienfuegos, Gonzalo ; Combas, Robert ; Comte, Serge ; Conroy, Stephen ; Couturier, Robert ; Couturier, Stéphane ; Crotty, Russell ; Cuenca, Arturo ; Curlet, François ; Dafflon, Stéphane ; Damisch, Gunter ; Debré, Olivier ; Degottex, Jean ; Delvoye, Wim ; Derges, Susan ; Devautour, Yoon Ja & Paul ; Dias, Antonio ; Dietman, Erik ; Domènech, Maribel ; Dorazio, Piero ; Dubuffet, Jean ; Duyckaerts, Eric ; Estève, Maurice ; Fabre, Jan ; Fanchon, Sylvie ; Fauguet, Richard ; Feher, Laszlo ; Fetting, Rainer ; Filliou, Robert ; Fontana, Lucio ; Friedmann, Gloria ; Fromanger, Gérard ; Gabritschevsky, Eugen ; Gargallo, Pablo ; Gfeller, Catherine ; Gilbert & George ; Glück, Anselm ; Graham, Dan ; Grosz, George ; Guerrero, Pep ; Haas, Michel ; Hamak, Herbert ; Hartung, Hans ; Hashimoto, Jacob ; Henning, Anton ; Hoffmann, Eduardo ; Hofmann, Hans ; Honetschläger, Edgar ; Huelin, Michel ; Hyber, Fabrice ; Irmer, Michael ; Jiménez, Cisco ; Ju Ming ; Judd, Donald ; Jusidman, Yishai ; Kappos, Marina ; Khazem, Jean-Pierre ; Klein, Micha ; Knorr, Karen ; Koons, Jeff ; Kreuter, Delphine ; Krystufek, Elke ; etc.
Frans & Engels
FIAC 2000, Paris expo - Porte de Versailles, Paris, 25 - 30 octobre 2000
boek